Bakhtin and Intergeneric Shift: The Case of Boris Godunov - Caryl Emerson (Studies in 20th & 21st Century Literature, 1984)
This essay draws on the historical and artistic image of Boris Godunov to illustrate Bakhtin's concept of "re-accentuation," or the transfer of literary images to new contexts. Russia of the 19th century was particularly well served by the Boris Tale. It inspired her first great popular historian, her greatest poet, and one of her greatest composers. Nikolai Karamzin's History of the Russian State (1816-29) ended with the Time of Troubles, and Karamzin's treatment of Boris Godunov became a model for biography in this new "romantic-national" type of history. Out of Karamzin's portrait Alexander Pushkin created his "romantic tragedy" Boris Godunov (1825), intended as a specifically national, Russian response to imported neoclassical norms in drama. Modest Mussorgsky adapted both Pushkin's and Karamzin's texts for the libretto to his greatest opera Boris Godunov (1869-74), which he offered as a national alternative to western operatic models, the first step toward a Russian "people's musical drama." In its three greatest expressions, the Boris Tale was thus a vehicle for generic innovation. Each treatment asserted a specifically Russian concept of genre in opposition to the European models then reigning in the three disciplines: German historiography, French drama, and Italian opera. Such innovative re-accentuations, or intergeneric "transpositions," are not easy to assess. They are vulnerable, as are translations, to charges of infidelity to earlier and more authoritative texts. This essay will argue, with Bakhtin's help, that the dialogue among these three texts is both calculated and complex; at the end, some suggestions are offered for reading cultural history through transposed or re-accentuated themes.
Keywords: Bakhtin theory; intergeneric shift; Boris Godunov; re-accentuation; Boris Tale; Nikolai Keramzin; History of the Russian State; Time of Troubles; national; nationalism; infidelity; cultural history